The Role of Teachers in Improving Student Discipline - Nikky Saputry; Fatqur Rohim; Irmawati, Irmawati (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2023)
This study aims to analyze the role of teachers in improving student discipline through the axiological approach of Islamic education. Using library research and School Action Research (SAR) methods along with a qualitative approach, data were obtained from recent and relevant literature sources. The results of the study show that teachers play a central role in shaping student discipline—as role models, mentors, and supervisors. The axiology of Islamic education emphasizes that discipline is not merely a set of rules, but an integral part of moral character (akhlaq). Through value-based learning, consistent supervision, and collaboration with parents, teachers can help students internalize the values of discipline. This research highlights the importance of teacher competence and consistency in shaping student discipline in accordance with Islamic values.